Efficacy and safety of local glucocorticoids for the treatment of acute radiation-induced intestinal injury: protocol of a multicenter randomized controlled trial - Li, Qianqian; Liu, Xiaofeng; Shao, Lichun; Bao, Xiaohua; Bai, Cheng; Ge, Junchen; Su, Dongshuai; Xu, Wenda; Jiang, Ran; Mu, Zhenbin; Dai, Hong; Piao, Bingguo; et al. (Frontiers in Pharmacology, 2025)
Background and aimsAcute radiation-induced intestinal injury (ARII) usually occurs after pelvic radiotherapy. Glucocorticoids are potentially effective for the treatment of ARII due to their anti-inflammatory properties, but the currently available evidence is insufficient. Herein, we have designed a multicenter randomized controlled trial (RCT) to explore the efficacy and safety of glucocorticoids for the treatment of ARII.MethodsOverall, 60 patients with ARII will be enrolled. Eligible patients will be stratified according to the grade of ARII and randomly assigned at a ratio of 1:1 to the routine treatment alone and in combination with local glucocorticoids groups. The primary endpoints include the recovery and improvement of ARII. The secondary endpoints include the recurrence and aggravation of ARII and adverse events of glucocorticoids.DiscussionThis RCT will provide high-quality evidence to clarify the role of local glucocorticoids for the treatment of ARII.Clinical trial registrationClinicalTrials.gov, identifier NCT06410443.